Panel Discussion 1 - Investing in open infrastructure and services: The benefits and challenges [video] - XIAO, Jesse (Institutional Knowledge at Singapore Management University, 2021)
Synopsis: There is a growing discussion about the need for open infrastructure in the scholarly communications landscape in order to avoid vendor lock in and high costs. However, open infrastructures also come with its own challenges, such as sustainable funding models, requirements of local expertise, and so on. This panel will present the perspectives of open infrastructure from different stakeholder communities and encourage engagement and discussion with the attendees.Moderator: Kathleen SHEARER, Executive Director, COAR Panellists: Jesse XIAO, Data and Scholarly Communication Librarian, The University of Hong Kong Libraries Kazu YAMAJI, Professor, National Institute of Informatics, Japan, and Vice Chairperson, COAR Executive Board Virginia BARBOUR, Co-Lead, QUT Office for Scholarly Communication, Director, Open Access Australasia